2019
DOI: 10.17644/sbd.491053
|View full text |Cite
|
Sign up to set email alerts
|

Orta Okul Öğrencileri İçin Fiziksel Aktivite Tutum Ölçeğinin Geliştirilmesi

Abstract: Çocukların fiziksel aktivite düzeyini yükseltmek ve fiziksel aktiviteye ilişkin olumlu tutum geliştirmelerini sağlamak için fiziksel aktiviteye yönelik bakış açıları hakkında bilgiye ihtiyaç vardır. Çocuğun fiziksel aktivite davranışını artırmak için öncelikle fiziksel aktiviteye ilişkin tutumu belirlemek ve sonuçlara göre uygulama stratejileri belirlemek gereklidir. Bu çalışmanın amacı, ortaokul öğrencilerinin fiziksel aktiviteye yönelik tutumlarını ölçmek için Fiziksel Aktiviteye Yönelik Tutum Ölçeği (FAYTÖ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…The obtained sub-dimensions were expressed as Affection (5 items), Willingness (7 items), Bene t (5 items), Socialization (4 items) and Self-Con dence (4 items). 1,2,3,4,5,6,7,22,23,24,25. the substances are encoded in reverse [24]. Cronbach's alpha was found to be 0.88 in pre-test measurements.…”
Section: Attitude Toward Physical Activity Scale (Apas)mentioning
confidence: 90%
See 1 more Smart Citation
“…The obtained sub-dimensions were expressed as Affection (5 items), Willingness (7 items), Bene t (5 items), Socialization (4 items) and Self-Con dence (4 items). 1,2,3,4,5,6,7,22,23,24,25. the substances are encoded in reverse [24]. Cronbach's alpha was found to be 0.88 in pre-test measurements.…”
Section: Attitude Toward Physical Activity Scale (Apas)mentioning
confidence: 90%
“…The APAS, which is used to determine primary school students' physical activity participation, was developed by Yıldızer et al (2019). It has been reported that the scale is a valid and reliable measurement tool for determining the physical activity attitudes of primary school students aged 12-15.…”
Section: Attitude Toward Physical Activity Scale (Apas)mentioning
confidence: 99%
“…Physical Activity Attitude Scale for Secondary School Students. The Physical Activity Attitude Scale for Secondary School Students scale, developed by Yıldızer et al [88], was used to measure students' physical activity attitudes. This scale consists of 5 sub-dimensions and 25 items: "Love" (5 items), "Willingness" (7 items), "Benefit (4 items)", "Socialization (5 items) and Self-Confidence (4 items).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…"1=Kesinlikle Katılmıyorum", "2=Katılmıyorum", "3=Kararsızım", "4=Katılıyorum", "5=Kesinlikle Katılıyorum" şeklinde maddelerden oluşmaktadır. Ölçeğin Cronbach Alfa iç tutarlılık katsayısının 0,91 olduğu belirtilmiştir (19). Bu çalışmada ölçeğin Cronbach Alfa iç tutarlılık katsayısı 0,729'dur.…”
Section: 32ortaokul öğRencileri Için Fiziksel Aktivite Tutum öLçeğiunclassified